Immediate total temporomandibular joint replacement with TMJ concepts prosthesis as an alternative for ameloblastoma cases (2014)
Ameloblastoma is a common epithelial odontogenic tumor, representing 1 to 3% of all cysts and tumors of the oral and maxillomandibular region. It has been more commonly found in the mandible than in the maxilla. Treatment of ameloblastoma is essentially surgical, ranging from conservative therapy such as enucleation, marsupialization, and curettage, to more radical approaches, including marginal, segmental, or composite resection. It has a high tendency to recur and, in some instances, has shown malignant development when treated inadequately. When resection is indicated, reconstructive measures must be considered. The aim of the present study is to report on 2 cases of large ameloblastomas of the solid/multicystic type that were treated by hemimandibulectomy and reconstructed with a novel technique consisting of a custom-made TMJ Concepts prosthesis (TMJ Concepts, Ventura, CA). The role and outcomes of custom-made temporomandibular joint prostheses in these circumstances are discussed.